Financial distress and corporate investment: The Japanese case in the 90s - Kazuo Ogawa (Osaka University, Institute of Social and Economic Research (ISER), 2003)
We examine quantitatively the extent to which financial distress in the 90s affected Japanese corporate investment. Based on the firm-level data that includes small, unlisted firms, we estimate investment function to measure the impact of financial distress on investment. We find that the firm's ratio of debt to total asset exerts a significantly negative effect on investment of small firms. We also find that lending attitude of financial institutions did affect investment behavior irrespective of firm size. The impact of lending attitude on investment is notably large for 1998 labeled 'credit crunch.'
Keywords: E22; E44; E51; 330; Financial distress; Debt hangover; Investment; External finance premium Lending channel; Investition; KMU; Kapitalstruktur; Japan; Finanzkrise